2003
DOI: 10.1095/biolreprod.102.013318
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Reperfusion of the Murine Testis Stimulates the Expression of Proinflammatory Cytokines and Activation of c-jun N-Terminal Kinase in a Pathway to E-Selectin Expression1

Abstract: Ischemia-reperfusion (IR) of the testis results in germ cell-specific apoptosis and can lead to aspermatogenesis. Germ cell-specific apoptosis after IR of the testis has been shown to be correlated with and dependent on neutrophil recruitment to the testis after IR. Studies that used E-selectin-deficient mice have demonstrated that E-selectin expression is critical for neutrophil recruitment to subtunical venules in the testis after IR and for the resultant germ cell-specific apoptosis. The present study inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 46 publications
4
104
2
Order By: Relevance
“…However, we observed prolonged ERK1/2 activation during the first 6-24 hr of reperfusion. Recently, Lysiak et al [17] and Turner et al [32] reported a differential time-course in the activation of another mitogen-activated protein kinase (MAPK), SAPK/JNK, in acute testicular torsion, which is similar to the pattern of ERK activation observed here. Therefore, MAPK activation appears to play a role in the pathophysiology of testicular I/R injury.…”
Section: Discussionsupporting
confidence: 83%
“…However, we observed prolonged ERK1/2 activation during the first 6-24 hr of reperfusion. Recently, Lysiak et al [17] and Turner et al [32] reported a differential time-course in the activation of another mitogen-activated protein kinase (MAPK), SAPK/JNK, in acute testicular torsion, which is similar to the pattern of ERK activation observed here. Therefore, MAPK activation appears to play a role in the pathophysiology of testicular I/R injury.…”
Section: Discussionsupporting
confidence: 83%
“…The minimal number of the samples was selected according to the basis of the previous studies (Lysiak et al 2003). Sham group received sham operation + 0.5 ml vehicle (corn oil) by gavage 5 min after the operation.…”
Section: Experimental Groups and Sample Collectionmentioning
confidence: 99%
“…The pathophysiology involves stimulating an intracellular signaling cascade in the endothelial cells of the ischeamic vessels. This results in neutrophil recruitment, an increase in intracellular reactive oxygen species (ROS), and eventual germ cell specific apoptosis (Turner & Miller, 1997;Lysiak et al, 2001Lysiak et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%